Mathematics

Remove all grouping symbols and combine like terms.
( 3x + x ^2) - { 4x^2 - 3x +[ 2x^2 - x - (5x^2 + 4x)]}
Thank you


Answers

yassautumn

4 years ago Comment

[latex]( 3x + x ^2) - (4x^2 - 3x +(2x^2 - x - (5x^2 + 4x)))=\\ 3x+x^2-4x^2+3x-(2x^2-x-5x^2-4x)=\\ -3x^2+6x-2x^2+x+5x^2+4x=\\ 11x[/latex]

lyssie11234

4 years ago Comment

[latex](3x+x^2)-\{4x^2-3x+[2x^2-x-(5x^2+4x)]\}\\\\=3x+x^2-\{4x^2-3x+[2x^2-x-5x^2-4x]\}\\\\=3x+x^2-\{4x^2-3x+[-3x^2-5x]\}\\\\=3x+x^2-\{4x^2-3x-3x^2-5x\}\\\\=3x+x^2-\{x^2-8x\}\\\\=3x+x^2-x^2+8x\\\\=11x[/latex]